Coping with shift work-related circadian disruption: A mixed-methods case study on napping and caffeine use in Australian nurses and midwives. (3rd June 2018) - Centofanti, Stephanie; Banks, Siobhan; Colella, Antonietta; Dingle, Caroline; Devine, Lisa; Galindo, Helen; Pantelios, Sophie; Brkic, Gorjana; Dorrian, Jillian
ABSTRACT: Introduction : Two of the most ubiquitous fatigue countermeasures used by shift-working nurses are napping and caffeine. This mixed-methods case study investigated the ways nurses and midwives utilised napping and caffeine countermeasures to cope with shift work, and associated sleep, physical health and psychological health outcomes. Materials and Methods : N  = 130 Australian shift-working nurses and midwives (mean age = 44 years, range = 21–67, 115F, 15M) completed the Standard Shiftwork Index. A sub-set of 22 nurses and midwives completed an in-depth interview. Results : Nearly 70% of participants reported napping. Those who napped during night shifts had significantly less total sleep time before ( F 2, 75  = 5.5, p  < 0.01) and between days off ( F 2, 82  = 3.9, p  < 0.05). By the end of the night shift, average hours of time awake were significantly less for prophylactic and on-shift nappers compared to non-nappers ( F 2, 85  = 97.2, p <  0.001). Since starting shift work, the percentage of high caffeine consumers (>400 mg/day) increased from 15% to 33% of the sample and an average of 4 (SD = 2) caffeinated beverages per day was reported. Increased caffeine consumption was associated with greater sleep disturbance ( r  = 0.26, p  < 0.05), psychological distress ( r  = 0.37, p  < 0.001), abdomen pain ( r  = 0.27, p  < 0.05) and weight gain since starting shift work ( r  = 0.25, p  < 0.05). Interviews confirmed these relationships and revealed that caffeine consumption on night shift was common, whereas napping on night shift was dependent on a number of factors including ability to sleep during the day. Conclusion : This study identified reasons shift workers chose to engage in or abstain from napping and consuming caffeine, and how these strategies related to poor sleep and health outcomes. Further research is required to help develop recommendations for shift workers regarding napping and caffeine consumption as fatigue countermeasures, whilst taking into account the associated hazards of each strategy.